Safety and efficacy of cryoablation for atrial fibrillation in young patients: A multicenter experience in the 1STOP project. Issue 2 (29th November 2022) - Bertaglia, Emanuele; Iacopino, Saverio; Verlato, Roberto; Arena, Giuseppe; Pieragnoli, Paolo; Tondo, Claudio; Molon, Giulio; Manfrin, Massimiliano; Perego, Giovanni B.; Rovaris, Giovanni; Rivezzi, Francesco; Mantica, Massimo; et al.
Abstract: Background: Atrial fibrillation (AF) is an uncommon arrhythmia in young adults without structural heart disease, and cryoballoon pulmonary vein isolation (CB‐PVI) is an important therapeutic strategy for rhythm control in patients with drug‐refractory AF. The aim of this analysis was to evaluate efficacy and safety of CB‐PVI in a large cohort of young patients in comparison with middle‐aged adults in a real‐world setting. Methods: From 2012 to 2020, a total of 3033 patients with AF underwent CB‐PVI and were followed prospectively in the framework of the 1STOP Clinical Service project, involving 34 Italian centers. Out of 3033 total 1STOP project subjects, a subgroup of 1318 patients were defined which included a YOUNG group (age ≤ 45 years; n  = 368) and a MIDDLE‐AGED group (age 60–65 years; n  = 950). Results: The acute success rate of PVI did not differ between the two cohorts (99.9 ± 1.3% vs. 99.8 ± 3.2%, p  = 0.415). There was no difference in procedural characteristics, and periprocedural complication rates were similar among the two cohort (1.9% vs. 2.3%, p  = 0.646). The 12‐month freedom from AF recurrence was 88.9% (95% confidence interval [CI]: 84.7–92.0) in the YOUNG cohort and 85.6% (95% CI: 82.9–88.0) in the MIDDLE‐AGED group. At 36‐month follow‐up, freedom from AF recurrence was 72.4% (65.5%–78.2%) and 71.8% (67.7%–75.6%), respectively with no significant difference among groups ( p  = 0.550). Conclusion: CB‐PVI had similar efficacy and safety in YOUNG and MIDDLE‐AGED patients. Younger age did not affect acute procedural results, complication rate, or AF recurrence after a single procedure. WHAT'S NEW?: This is the first multicenter analysis to evaluate the differences in efficacy and safety of a single ablation technique (cryoballoon pulmonary veins isolation) for atrial fibrillation between young and middle‐aged patients. Our analysis demonstrated the same rate of acute success, freedom from recurrent atrial fibrillation between young and middle‐aged patients, despite (as expected) older patients having more comorbidities. Safety outcomes of the procedure did not differ between young and middle‐aged patients, with a very low complication rate overall in both cohorts. The rate of repeat ablations following the index procedure was higher in young as compared to middle‐aged